Exchanging fluids The sociocultural implications of microbial, cultural, and ethnic admixture in Latin America - Cabeza de Baca, Tomás (2020)
Knowledge of evolutionary influences on patterns of human mating, social interactions, and differential health is increasing, yet these insights have rarely been applied to historical analyses of human population dynamics. The genetic and evolutionary forces behind biases in interethnic mating and in the health of individuals of different ethnic groups in Latin America and the Caribbean since the European colonization of America are still largely ignored. We discuss how historical and contemporary sociocultural interactions and practices are strongly influenced by population-level evolutionary forces. Specifically, we discuss the historical implications of functional (de facto) polygyny, sex-biased admixture, and assortative mating in Latin America. We propose that these three evolutionary mechanisms influenced mating patterns, shaping the genetic and cultural landscape across Latin America and the Caribbean. Further, we discuss how genetic differences between the original populations that migrated at different times into Latin America contributed to their accommodation to and survival in the different local ecologies and interethnic interactions. Relevant medical and social implications follow from the genetic and cultural changes reviewed.